The culture of legality as an interdisciplinary subject - Andrade Guevara, Victor Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
This article aims to develop a reflection on the interdisciplinary nature of the concept "culture of legality" when it becomes the matter of social science research. My position is based, firstly, on the review of the main social sciences conceptions concerning interdisciplinarity, which I try to differentiate vis à vis the transdisciplinarity concept. It has been linked to the complex thinking. Also it has been emphasized the need to maintain a constant relation between theoretical construction and empiric research according to Jean Michel Berthelot´s epistemological principles. Next, I continue with a breve review of the culture of legality when it is treated by diverse academic disciplines such as Law, Political Science, Sociology or Anthropology, as well as the ideas provided by Political Philosophy. Finally, from previous reflections, some methodological approaches linked to the study of the culture of legality in a region of the State of Veracruz in Mexico are mentioned.